Overall Transfer Thermal Value (OTTV) index assessment on 4G11 Tower, Ministry of Women Family and Community Development, Putrajaya Malaysia / Amirul Amin Ismail and Azman Zainonabidin - Ismail, Amirul Amin; Zainonabidin, Azman (Universiti Teknologi MARA, Perak, 2016)
In the Eleventh Malaysia Plan, Malaysia will be pioneering a sustainable city development by retrofitting all Government buildings to be energy efficient. Overall Thermal Transfer Value (OTTV) is a measuring tool of thermal efficiency for building envelope. A case study on iconic 4G11 Tower is carried out to determine the possibility of improving OTTV assessment for existing high-rise office building thus enhance the building’s overall efficiency. Through this exercise, several variables influence the OTTV score such as U-Value, Shading Coefficient (SC) and Window-to-Wall Ratio (WWR). Characterised by Baseline Design, MS1525 Design and Platinum Design, this will be a precedent of OTTV assessment for high-rise office building typology.